2010
DOI: 10.11646/zootaxa.2364.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic revision of the Brazilian Atlantic Forest Atractus (Reptilia: Serpentes: Dipsadidae)

Abstract: Dipsadine snakes of the genus Atractus are endemic to the Neotropical region, occurring from Panama to Argentina. Currently, the taxonomic status of most species of the genus is unclear and previous attempts of taxonomic revisions have been local in scale. In this paper we evaluate the taxonomic status of the Brazilian Atlantic Forest species of Atractus based on meristic, morphometric, maxillary dentition, and hemipenis characters. Quantitative and qualitative analyses suggest the recognition of one new speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 0 publications
1
40
0
5
Order By: Relevance
“…The genus Atractus Wagler, 1828, comprises about 130 small fossorial snake species that occur in South America (Giraudo and Scrocchi, 2002;Myers, 2003;Passos et al, 2010). Atractus pantostictus is an endemic species from Brazil (B ernils and Costa, 2012), occurring in central and south-eastern Brazil, in the states of Goi as, Distrito Federal, Tocantins, Minas Gerais and São Paulo, and inhabits areas of Cerrado and Cerrado/Submontane to Lower Montane semi-deciduous forest transition zones (Passos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Atractus Wagler, 1828, comprises about 130 small fossorial snake species that occur in South America (Giraudo and Scrocchi, 2002;Myers, 2003;Passos et al, 2010). Atractus pantostictus is an endemic species from Brazil (B ernils and Costa, 2012), occurring in central and south-eastern Brazil, in the states of Goi as, Distrito Federal, Tocantins, Minas Gerais and São Paulo, and inhabits areas of Cerrado and Cerrado/Submontane to Lower Montane semi-deciduous forest transition zones (Passos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Atractus pantostictus is an endemic species from Brazil (B ernils and Costa, 2012), occurring in central and south-eastern Brazil, in the states of Goi as, Distrito Federal, Tocantins, Minas Gerais and São Paulo, and inhabits areas of Cerrado and Cerrado/Submontane to Lower Montane semi-deciduous forest transition zones (Passos et al, 2010). The reproductive biology of most species is poorly known, and available data are mainly from very small samples (Fernandes and Puorto, 1993;Oliveira, 1993, 1999;Cassimiro et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…suggested putative affinities of A. insipidus and A. punctiventris with other cis-Andean congeners (A. altagratiae, A. pantostictus Puorto 1993, andAtractus ronnie Passos, Fernandes, andBorges-Nojosa 2007). Passos et al (2010b) assigned the last three species to the A. pantostictus species group. However, the everted conditions of the hemipenes for A. insipidus is so far unknown (Passos et al 2013a), and the association made by was based on specimens identified tentatively as A. insipidus by Silva (1993) and Silva et al (2005;now A. boimirim).…”
Section: Discussionmentioning
confidence: 99%
“…Terminology for hemipenial descriptions follows Dowling and Savage (1960) and Zaher (1999) with a few minor adaptations. We follow Passos et al (2009e) and Passos et al (2010b) with respect to conditions of the morphological characters used in diagnosis and description. …”
Section: Geographical Data and South American Biogeographymentioning
confidence: 99%
See 1 more Smart Citation